Expanded morphological description of the Drogon’s False Garden Lizard, Pseudocalotes drogon (Squamata: Agamidae) from Peninsular Malaysia - Hong, Zijia; Anuar, M.s. Shahrul; Grismer, L. Lee; Quah, Evan S. H. (Zootaxa, 2024)
Species in the genus Pseudocalotes are generally rare and known only from a few specimens. Pseudocalotes drogon was described based on a single male from Fraser’s Hill, Pahang, Peninsular Malaysia. During a recent field survey at Fraser’s Hill, a female specimen was collected and identified as P. drogon based on morphological characters and a molecular phylogenetic analysis. The morphological description of P. drogon is expanded here, based on the male holotype and the newly collected female specimen.